The Implementation of Religious Values in Social Life - Zalfa, Syahgita (Maliki Interdisciplinary Journal, 2026)
The implementation of religious values in social life plays an important role in shaping balanced behavior and social interactions within society. Religious teachings serve as guidelines in fostering mutual respect, honesty, social awareness, and responsibility within the community. This study aims to understand how religious values are applied in social life and their influence on interactions among individuals. The method used in this research is descriptive qualitative with a literature review and social observation approach. The results show that the implementation of religious values can be reflected through mutual respect, cooperation, maintaining harmony, and increasing moral awareness among society. However, the application of religious values in social contexts still faces challenges such as the impact of modernization and decreasing social empathy. Therefore, the active role of families, educational institutions, and community leaders is needed to strengthen religious values in order to create a balanced and ethical social life.